A study on a telo21 G-quadruplex DNA specific binding ligand: enhancing the molecular recognition ability via the amino group interactions. Issue 36 (4th June 2018) - Li, Dongli; Hou, Jin-Qiang; Long, Wei; Lu, Yu-Jing; Wong, Wing-Leung; Zhang, Kun
Abstract : A significant fluorescent signal enhancement attributed to hydrogen-bonding interactions through the amino groups of a small binding ligand in the G-quartets (binding energy: −6.2 kcal mol −1 ). Abstract : A symmetric ligand is synthesized composed of a core N -methylpyridinium scaffold and two para -substituted benzyl groups through a flexible ethylene bridge to form a novel three-ring-conjugated system. The ligand system was found to have only weak background fluorescent signal in aqueous or physiological conditions and exhibited strong fluorescent signal enhancement targeting at telo21 G-quadruplex structure rather than other types of nucleic acids. The comparison study with two terminal groups (–N(CH3 )2 versus –SCH3 ) indicates that the stimulated signal enhancement of specific binding is probably attributed to the hydrogen-bonding interactions through the amino groups in the G-quartets. The docking result illuminates the experimental observation that the ligand system showed only weak fluorescent signals in aqueous or physiological conditions while exhibiting a strong fluorescent signal upon binding to the telo21 G-quadruplex structure (binding energy: −6.2 kcal mol −1 ).